2021
DOI: 10.2320/matertrans.mt-m2021107
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Pure Metals with Liquid Sodium and Liquid Tin

Abstract: This study aims to control the wettability of pure transition metals by liquid sodium or liquid tin. Such wettability was evaluated by measuring the contact angles with the droplet method. Pure titanium, iron, nickel, copper, and molybdenum metals were selected as specimens in this experiment. All experiments were conducted in an environment with high pure argon gas and extremely low moisture to avoid the influence of oxygen on the liquid metals. The measurement temperature was just above the melting temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Theoretical calculations of the interface confirmed no significant change in the atomic interaction at the interface between the on-top and hollow sites of the metal substrate. [2] Therefore, this study performs the calculations at the on-top site.…”
Section: Cluster Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical calculations of the interface confirmed no significant change in the atomic interaction at the interface between the on-top and hollow sites of the metal substrate. [2] Therefore, this study performs the calculations at the on-top site.…”
Section: Cluster Modelsmentioning
confidence: 99%
“…The results showed that the contact angle relates to the atomic interactions at the interface. [1][2][3][4] Therefore, we considered that one way to control wettability is to control the electronic state, which is the atomic interaction at the interface. Furthermore, we focused on ion implantation technology to change the electronic state of metal surfaces.…”
Section: Introductionmentioning
confidence: 99%